Rare Postoperative Complication of Esophageal Atresia after Open Thoracotomy Repair in Newborn-Lung Torsion: A Case Report - Szymon Gryboś; Viera Karaffová; Katarina Klapačová (MDPI AG, 2024)
In this case report, we described a rare complication-lung torsion after esophageal atresia repair in a newborn. Torsion of the lung is a critical condition in which either the entire lung or a lung lobe twists, leading to occlusion of blood vessels and airways. The patient's clinical condition was poor after the primary operation. An emergency thoracotomy showed 180° torsion of the right upper lobe (RUL) and right middle lobe (RML). After detorsion, perioperatively, the lung was gradually reperfused and had a normal appearance. After surgery, the patient was unstable, which culminated in a fatal end (bradycardia, reperfusion injury). Immediate intervention can preserve the affected lung or lung lobe. However, pulmonary torsion typically has a poor prognosis due to misdiagnosis and delayed treatment. Additionally, diagnosis in the neonatal period is even more challenging because the clinical symptoms are nonspecific. In any case, the question is whether detorsion is the right solution or whether a segmentectomy is necessary.